Controlled micellar disassembly of photo- and pH-cleavable linear-dendritic block copolymers - Kalva, Nagendra; Parekh, Nimisha; Ambade, Ashootosh V. (Polymer Chemistry, 2015)
A linear-dendritic block copolymer with both photo-and pH-cleavable linkages at the junction between the hydrophobic dendron and hydrophilic linear polymer was synthesised. The photocleavable o-nitrobenzyl group attached to alkyne was introduced at the focal point of polyester dendron and acid-degradable acetal linkage with terminal azide was introduced at one end of linear polyethylene glycol. The two segments were connected using click chemistry. The copolymer was found to self-assemble into micelle-like aggregates in dilute aqueous solution. Stimuli-responsive disassembly of the aggregates was studied by monitoring fluorescence emission of the encapsulated hydrophobic dye and dynamic light scattering (DLS). Products of acetal cleavage at acidic pH were analyzed by gel permeation chromatography and NMR spectroscopy. The photo and pH stimuli were applied separately as well as simultaneously to study the rate of dye release. The synergistic effect of the two stimuli on dye release was demonstrated and the non-cytotoxic nature of the polymer was shown using the MTT assay. Cell uptake of DOX-loaded micelles and photo-induced release of the drug resulting in significantly higher cytotoxicity than by free DOX was demonstrated using MDA-MB-231 cells.

Controlled synthesis of end-functionalized mannose-6-phosphate glycopolypeptides for lysosome targeting - Das, Soumen; Parekh, Nimisha; Mondal, Basudeb; Sen Gupta, Sayam (ACS Macro Letters, 2016)
The ubiquitous expression of the mannose-6-phosphate receptor on the majority of human cells makes it a valid target in the quest to deliver therapeutics selectively to the lysosome. In this work end-functionalized polyvalent mannose-6-phosphate glycopolypeptides (M6P-GPs) with high molecular weights (up to 22 kDa) have been synthesized via NCA polymerization. These synthetic M6P-GPs were found to display minimal toxicity to cells in vitro and show exceptional selectivity for trafficking into lysosomes in various cell lines. Comparison of the cellular uptake behavior of M6P-GP and the corresponding mannose-GP polymer reveals that incorporation of the phosphate moiety at the 6-position of mannose completely alters its trafficking behavior and becomes exclusively lysosome specific. We also demonstrate that trafficking of M6P-GPs in mammalian cells is likely associated with the CI-MPR receptor pathway.

Orientation effect induced selective chelation of Fe2+ to a glutamic acid appended conjugated polymer for sensing and live cell imaging - Senthilkumar, T.; Parekh, Nimisha; Nikama, Shrikant B.; Asha, S. K. (Journal of Materials Chemistry B, 2016)
Intracellular detection and imaging of labile iron(II) pools is very important in tracking physiological processes that demand new and rapid sensing probes. In this report, we present a water soluble polymer based probe for the fluorescence sensing and live cell imaging of labile Fe2+ ions with high selectivity for the first time. The polymer probe was based on conjugated polyfluorene which was appended with amino acid (L-glutamic acid). The biocompatibility of the polymer was confirmed from an MTT assay which demonstrated >90% cell viability even at 300 mu g ml(-1) loading of polymers. Simple glutamic acid did not show selectivity towards any of the divalent ions. However, glutamic acid appended polyfluorene exhibited selective chelation to Fe2+ ions resulting in immediate sensing activity for Fe2+ ions in water and living cells with fluorescence turn-off response. The limit of detection of the PF-Ph-GA polymer probe was 46 (+/- 2) nM which indicated high sensitivity for Fe2+ over other ions reported in the literature. The polymer also exhibited improved sensing activity in the range of intracellular pH (5-9) which is advantageous in differentiating endogenous changes. The probe was successfully applied for the fluorescence imaging of intracellular and supplemented labile iron(II) pools in living HeLa cells.

Self- assembly of isomannide-based monoesters of C18-fatty acids and their cellular uptake studies - Dhasaiyan, Prabhu; Parekh, Nimisha; Reddy, T. Vijai Kumar; Rani, G. Sandhya; Devi, B. L. A. Prabhavathi; Bhagavatula L. V. Prasad (RSC Advances, 2016)
The self-assembling behavior of oleic, elaidic and stearic acid-isomannide glycolipids is revealed. Amongst these, oleic and elaidic acid-based isomannide lipids self-assembled to form microspheres which were efficiently taken up by cancer cell lines enabling their usage for drug delivery applications.

Tunable nanocarrier morphologies from glycopolypeptide-based amphiphilic biocompatible star copolymers and their carbohydrate specific intracellular delivery - Pati, Debasis; Das, Soumen; Patil, Naganath G.; Parekh, Nimisha; Anjum, Dalaver H.; Dhaware, Vinita; Ambade, Ashootosh V.; Sen Gupta, Sayam (Biomacromolecules, 2016)
Nanocarriers with carbohydrates on the surface represent a very interesting class of drug-delivery vehicles because carbohydrates are involved in biomolecular recognition events in vivo. We have synthesized biocompatible miktoarm star copolymers comprising glycopolypeptide and poly(e-caprolactone) chains using ring-opening polymerization and ``click chemistry''. The amphiphilic copolymers were self-assembled in water into morphologies such as nanorods, polymersomes, and micelles with carbohydrates displayed on the surface. We demonstrate that the formation of nanostructure could be tuned by chain length of the blocks and was not affected by the type of sugar residue. These nanostructures were characterized in detail using a variety of techniques such as TEM, AFM, cryogenic electron microscopy, spectrally resolved fluorescence imaging, and dye encapsulation techniques. We show that it is possible to sequester both hydrophobic as well as hydrophilic dyes within the nanostructures. Finally, we show that these noncytotoxic mannosylated rods and polymersomes were selectively and efficiently taken up by MDA-MB-231 breast cancer cells, demonstrating their potential as nanocarriers for drug delivery.

Amphiphilic mannose-6-phosphate glycopolypeptide-based bioactive and responsive self-assembled nanostructures for controlled and targeted lysosomal cargo delivery - Mondal, Basudeb; Pandey, Bhawana; Parekh, Nimisha; Panda, Sidharth; Dutta, Tahiti; Padhy, Abinash; Sen Gupta, Sayam (Biomaterials Science, 2020)
Receptors of carbohydrate mannose-6-phosphate (M6P) are overexpressed in specific cancer cells (such as breast cancer) and are also involved in the trafficking of mannose-6-phosphate labeled proteins exclusively onto lysosomes via cell surface M6P receptor (CI-MPR) mediated endocytosis. Herein, for the first time, mannose-6-phosphate glycopolypeptide ((M6P)GP)-based bioactive and stimuli-responsive nanocarriers are reported. They are selectively taken up via receptor-mediated endocytosis, and trafficked to lysosomes where they are subsequently degraded by pH or enzymes, leading to the release of the cargo inside the lysosomes. Two different amphiphilic M6P block copolymers (M6P)GP(15)-(PPO44)-P-A and (M6P)GP(15)-(PCL25)(2) were synthesized by click reaction of the alkyne end-functionalized (M6P)GP(15) with pH-responsive biocompatible azide end-functionalized acetal PPO and azide end-functionalized branched PCL, respectively. In water, the amphiphilic M6P-glycopolypeptide block copolymers self-assembled into micellar nanostructures, as was evidenced by DLS, TEM, AFM, and fluorescence spectroscopy techniques. These micellar systems were competent to encapsulate the hydrophobic dye rhodamine-B-octadecyl ester, which was used as the model drug. They were stable at physiological pH but were found to disassemble at acidic pH (for (M6P)GP(15)-(PPO44)-P-A) or in the presence of esterase (for (M6P)GP(15)-(PCL25)(2)). These (M6P)GP based micellar nanoparticles can selectively target lysosomes in cancerous cells such as MCF-7 and MDA-MB-231. Finally, we demonstrate the clathrin-mediated endocytic pathway of the native FL-(M6P)GP polymer and RBOE loaded (M6P)GP micellar-nanocarriers, and selective trafficking of MCF-7 and MDA-MB-231 breast cancer cell lysosomes, demonstrating their potential applicability toward receptor-mediated lysosomal cargo delivery.

Silk fibroin and recombinant elastin blend nano-coatings for implantable medical devices - Joseph, Emmanuel; Kane, Kartiki; Parekh, Nimisha; Nisal, Anuya; Janorkar, V. Amol (Materials Today Communications, 2022)
Silicone breast implants are conventionally used to reconstruct the shape and size of the breast in breast cancer patients. However, rate of failure of implants due to formation of capsular contracture is significantly high. Recent studies have shown that coating the surface of the implant with a biocompatible polymer can mitigate this risk. Here, we have modified the surface of implant using a biocompatible natural biopolymer silk fibroin (SF). Further, we have developed formulations of SF with a recombinantly produced elastin-like-peptide (ELP) and compared their performance with a known anti-fouling hydrophilic polymer - polyethylene oxide (PEO). Microscopic and spectroscopic characterization confirm the formation of uniform coatings. These coatings have been also characterized for their ability to resists crack formation. Further, the coatings have been evaluated for their biological performance. Our studies show that addition of 25 wt% of ELP to SF significantly enhances the crack resistance for the coatings. In addition, SF/ELP coatings reduce the adsorption of blood plasma proteins by more than 80 %. Preliminary analysis shows that the SF/ELP blend coatings are non-cytotoxic and support adhesion, growth and proliferation of fibroblast cells. The study therefore demonstrates that SF/ELP coatings have the potential to mitigate the risk of breast implant failure.
Keywords: Blood plasma; Crack resistance; Protein adsorption; Recombinant elastin; Silk fibroin

Superior processability of Antheraea mylitta silk with cryo-milling: performance in bone tissue regeneration - Parekh, Nimisha; Bijosh, C. K.; Kane, Kartiki; Panicker, Alaka; Nisal, Anuya; Wangikar, Pralhad; Agawane, Sachin (International Journal of Biological Macromolecules, 2022)
Non-mulberry silk polymers have a promising future in biomedical applications. However, the dissolution of nonmulberry silk fiber is a still challenge and this poor processability has limited the use of this material. Here, we report a unique protocol to process the Antheraea mylitta (AM) silk fiber. We have shown that the cryo-milling of silk fiber reduces the beta sheet content by more than 10% and results in an SF powder that completely dissolves in routine solvents like trifluoroacetic acid (TFA) within few hours to form highly concentrated solutions (\~20 wt %). Further, these solutions can be processed using conventional processing techniques such as electrospinning to form 3D scaffolds. Bombyx mori (BM) silk was used as a control sample in the study. In-vitro studies were also performed to monitor cell adhesion and proliferation and hMSCs differentiation into osteogenic lineage. Finally, the osteogenic potential of the scaffolds was also evaluated by a 4-week implantation study in rat calvarial model. The in-vitro and in-vivo results show that the processing techniques do not affect the biocompatibility of the material and the AM scaffolds support bone regeneration. Our results, thus, show that cryo-milling facilitates enhanced processability of non-mulberry silk and therefore expands its potential in biomedical applications.
Keywords: Bone tissue engineering; Calvarial defect; hMSCs; Non-mulberry silk fiber; Processing technique